Pengaruh Hidden Curriculum dan Disiplin Terhadap Religiusitas Siswa SMPN 1 Mlarak Ponorogo - Ihwan Mahmudi; Taufik Abdullah Attamimi (Universitas Cokroaminoto Yogyakarta, 2020)
This research aims to determine the effect of hidden curriculum and discipline on student religiosity. This research approach uses a quantitative approach with questionnaire survey methods. Sampling uses simple random sampling from an affordable population, namely class VIII students who are part of the target population, namely all students of SMPN 1 Mlarak Ponorogo. The sample of this study was 114 out of 170 students. Data analysis techniques using descriptive analysis, prerequisite tests, and hypothesis testing using multiple regression analysis of two predictors. The results of the H1 study with a calculated t value of 2,404 and sig. 0.010 / 2 = 0.005 (p <0.05), H0 is rejected which means that there is an influence of hidden curriculum on religiosity. H2 with a value of t count 1.944 and sig. 0.054 / 2 = 0.027 (p <0.05), H0 is rejected which means there is a disciplined influence on religiosity. And H3 with an F value of 27.095 and sig. 0.000 (p <0.05), H0 is rejected which means that there is a hidden influence of the curriculum and discipline simultaneously on the religiosity of students of SMPN 1 Mlarak Ponorogo.